Analysis of Molecular Orientation in Organic Semiconducting Thin Films Using Static Dynamic Nuclear Polarization Enhanced Solid‐State NMR Spectroscopy. Issue 47 (25th October 2017) - Suzuki, Katsuaki; Kubo, Shosei; Aussenac, Fabien; Engelke, Frank; Fukushima, Tatsuya; Kaji, Hironori
Abstract: Molecular orientation in amorphous organic semiconducting thin‐film devices is an important issue affecting device performance. However, to date it has not been possible to analyze the "distribution" of the orientations. Although solid‐state NMR (ssNMR) spectroscopy can provide information on the "distribution" of molecular orientations, the technique is limited because of the small amount of sample in the device and the low sensitivity of ssNMR. Here, we report the first application of dynamic nuclear polarization enhanced ssNMR (DNP‐ssNMR) spectroscopy for the orientational analysis of amorphous phenyldi(pyren‐1‐yl)phosphine oxide (POPy2 ). The 31 P DNP‐ssNMR spectra exhibited a sufficient signal‐to‐noise ratio to quantify the distribution of molecular orientations in amorphous films: the P=O axis of the vacuum‐deposited and drop‐cast POPy2 shows anisotropic and isotropic distribution, respectively. The different molecular orientations reflect the molecular origin of the different charge transport behaviors. Abstract : The orientation of organic semiconducting molecules in an amorphous thin film was studied by static dynamic nuclear polarization enhanced solid‐state NMR spectroscopy. In a vacuum‐deposited film of the electron transport material POPy2, the P=O axis tends to orient perpendicular to the substrate. There is a close relationship between the orientational distribution and charge transport behavior.